Individualizing musical tempo to spontaneous rates maximizes music-induced hypoalgesia - Yi, Winbo; Palmer, Caroline; Serian, Angela; Roy, Mathieu (Pain, 2025)
Music has long been recognized as a noninvasive and cost-effective means of reducing pain. However, the selection of music for pain relief often relies on intuition rather than on a scientific understanding of the impact of basic musical attributes on pain perception. This study examines how a fundamental element of music—tempo—affects its pain-relieving properties. One important finding in research on temporal dynamics of music is that people tend to sing or tap at a characteristic rate when asked to produce a simple melody. This characteristic rate, known as the spontaneous production rate (SPR), is consistent across different rhythm production tasks and may reflect the output of an endogenous oscillator. According to dynamical systems theory, SPRs represent optimal efficiency, minimizing energy expenditure while maximizing behavioral accuracy. This study examined whether aligning music tempo with individual SPRs could enhance the hypoalgesic effects of music. First, participants' SPRs were measured by asking them to produce a familiar melody at a comfortable rate. Next, they were asked to rate painful thermal stimulations under 4 conditions: music modified to match participants' SPR, music modified to be 15% faster or 15% slower than participants' SPR, and silence. Results revealed that musical tempos matching participants' SPR produced stronger reductions in pain compared to faster or slower tempo conditions, supporting the hypothesis that musical tempo aligned with individual rates is optimal for reducing pain. These findings underscore the individual-specific effects of musical tempo on pain perception, offering implications for personalized pain management strategies.
Gesehen am 21.08.2025